Medical Economics: End the FDA (Food and Drug Administration) - Romanach, John; Block, Walter E. (Journal the Winners: Economics, Business, Management, and Information System Journal, 2017)
The aim of this research is to know what FDA was done to get pure food and drug. Was it to put all the eggs in one basket and entrust the objective to a monopolistic agency which suffers no financial losses when it errors or would the authors be better off relying on a private, competitive certification industry, the firms of which can earn profits for accurate assessments and losses for erroneous ones? Ensuring the quality of pharmaceuticals was concerned, the best and most efficient means toward that end was reliance on free enterprise. The method used was the literature review by applying what the authors knew about the difference between competition and monopoly to an arena where all too seldom was it applied. It finds that the FDA cannot eliminate risk; only deny people from taking the calculated risk in the hope of curing disease. Legislation such as the Compassionate Freedom of Choice Act has been introduced with the intention of empowering patients to make informed decisions and allow them to take drugs not approved by the FDA.